Uses and Gratifications : Twitter Tetap Menjadi Primadona - Andhika Febi Hardina; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
This research discusses the social media Twitter, which is the first platform to search for the latest information or news. This is backed up by the large amount of news or information circulating on online news portals, often sourced from the social media Twitter. The purpose of this literature review is to see how Twitter was chosen by social media users as a place to fulfill their information needs. The scope of this research is in the mass media communication circle using Uses & Gratifications Theory (UGT) to explain why users choose their media to complement their needs. This study uses an in-depth interview exploratory description method. Data collection from journals or previous research is carried out based on the context and cases where the data and information are needed in this study. In addition, this study uses an exploratory description method of in-depth interviews with four respondents who use social media Twitter. Questions are given in a structured manner. The result of this research is that there is a new motivation for people to use Twitter.